Recognising Multi-textualism: Rethinking New Zealand's Legal History - Boast, Richard (Victoria University of Wellington Law Review, 2019)
In this article the author discusses various written agreements that the New Zealand government has entered into with Māori since the signing of the Treaty of Waitangi in 1840. It is argued that the legal history of New Zealand is more "multi-textual", and more like Canada, the United States, and Argentina than is often thought. It is argued also that the process of agreement-making has been a continuously evolving one and at the present day is more important than ever. The article distinguishes between various types of Crown-Māori agreements and explores which of them are more Treaty-like than others.